Efektifitas Yoga Nidra Untuk Mengurangi Tingkat Kecemasan Pada Ibu Hamil - Alfie Ardiana Sari; Ratih Kumorojati (MEDIA ILMU KESEHATAN, 2025)
Background: Pregnancy often cause discomfort, anxiety, and fear due to hormonal and physical changes in mothers. One way to overcome these problems is through yoga. Practicing yoga during pregnancy is a useful self-help method to reduce discomfort, support the birthing process, and prepare mentally for the postpartum period. One yoga technique, Yoga Nidra, a form of Savasana, helps relax the body physically and psychologically.Objective: To determine the effectiveness of Yoga Nidra in reducing anxiety levels among pregnant women at Puskesmas Kasihan I.Methods: This quantitative study used a quasi-experimental design with a pretest–posttest without control. The population consisted of 53 pregnant women at Puskesmas Kasihan I. The sample included 16 third-trimester women selected randomly and given Yoga Nidra four times. Primary data were collected using questionnaires, while secondary data came from medical records. Data were analyzed using a paired sample t-testResults: The Sig (2-tailed) value was 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. Conclusion: Yoga Nidra effectively reduces anxiety among pregnant women at Puskesmas Kasihan I.